2006
DOI: 10.1111/j.1365-2893.2005.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of lamivudine in patients with severe acute or fulminant hepatitis B, a multicenter experience

Abstract: Acute hepatitis B progresses to liver failure with the need of liver transplantation in about 1% of cases. We treated patients with severe acute or fulminant hepatitis B with lamivudine in an attempt to prevent hepatitis B virus (HBV) reinfection after potential liver transplantation. Since September 2000, 17 patients with severe acute or fulminant HBV infection were treated with 100 or 150 mg lamivudine daily once we had evidence for a severe course as indicated by an INR >2.0. These were compared to a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 33 publications
4
127
0
13
Order By: Relevance
“…This explains why some patients present with borderline or nondetectable HBV DNA, a situation that may be anticipated more often when a prolonged delay exists between the onset of symptoms and first assessment. 12,14 It can be argued that complete clinical recovery in these instances may depend more on the adequacy of hepatocellular regeneration rather than the rate or degree to which viral replication is suppressed by antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why some patients present with borderline or nondetectable HBV DNA, a situation that may be anticipated more often when a prolonged delay exists between the onset of symptoms and first assessment. 12,14 It can be argued that complete clinical recovery in these instances may depend more on the adequacy of hepatocellular regeneration rather than the rate or degree to which viral replication is suppressed by antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of lamivudine therapy in 17 patients with severe or fulminant hepatitis B, treatment was associated with a significantly lower rate of encephalopathy and need for transplantation when compared with historical controls. 12 In a randomized controlled trial of lamivudine versus placebo in 71 patients with acute hepatitis and jaundice (bilirubin >5 mg/dL), serum HBV DNA levels decreased more rapidly in the lamivudine group, but higher rates of clinical and biochemical improvement were not observed. 13 Recently, data on 61 patients with fulminant liver failure due to acute hepatitis B was reported from the US Acute Liver Failure Study Group.…”
Section: Severe or Protracted Acute Viral Hepatitismentioning
confidence: 99%
“…Tillman et al [55] reported that Lamivudine may prevent the progression of severe hepatitis B to liver failure by decreasing HBV DNA load, reducing inflammatory reaction and improving liver function when administered early enough.…”
Section: Review Of Literaturementioning
confidence: 99%
“…These studies are small and LAM has been used in most, which has been found to improve survival. However, a randomized study did not demonstrate any difference in the rate of biochemical improvement or of HBsAg loss [77,78]. Several years ago, a randomized trial was conducted in Greece in patients with acute icteric hepatitis B using IFN-a 2b with no benefit, since all patients lost HBsAg and seroconverted to anti-HBs [79].…”
Section: Acute and Fulminant Hepatitis Bmentioning
confidence: 99%